Desenvolvimento de pastas cimentantes utilizando cimentos portland compostos para cimentação de poços petrolíferos - Belém, Francisco Aldemir Teles (2010)
The Compound Portland cements are commonly used in construction, among them stand out the CPII-Z, CPII-F and CPIV. These types of cement have limited application on oil well cementing, having its compositional characteristics focused specifically to construction, as cement for use in oil wells has greater complexity and properties covering the specific needs for each well to be coated. For operations of oil wells cementing are used Portland cements designed specifically for this purpose. The American Petroleum Institute (API) classifies cements into classes designated by letters A to J. In the petroleum industry, often it is used Class G cement, which is cement that meets all requirements needed for cement from classes A to E. According to the scenario described above, this paper aims to present a credible alternative to apply the compound cements in the oil industry due to the large availability of this cement in relation to oil well cements. The cements were micro structurally characterized by XRF, XRD and SEM tests, both in its anhydrous and hydrated state. Later technological tests were conducted to determine the limits set by the NBR 9831. Among the compound cements studied, the CPII-Z showed satisfactory properties for use in primary and secondary operations of oil wells up to 1200 meters cementing